Synchronous primary parotid tuberculosis and EBV-associated primary lymphoepithelial carcinoma - Anandhi Anbalagan; Deepti Jain; Senthil Kumar Ravichander (Indian Journal of Pathology and Microbiology)
A 48-year-old gentleman presented with complaints of neck swelling in the parotid region for 2 years. Diagnostic nasal endoscopy and video laryngeal stroboscopy were normal, and positron emission tomography scan showed no other primary lesion. The lesion with tail of parotid was excised and sent for histopathological examination. Part of the tissue was also sent for diagnosis of tuberculosis by polymerase chain reaction (PCR) as it is a very common disease in South Asian countries. At this point, differentials considered were undifferentiated primary carcinoma, metastatic undifferentiated nasopharyngeal carcinoma, and primary lymphoepithelial carcinoma. At the same time, PCR for tuberculosis came positive with rifampicin sensitive in drug resistance testing. EBV by ISH testing came out to be positive. Final diagnosis of primary lymphoepithelial carcinoma with co-existing tuberculosis of parotid was made. The patient was started on antitubercular therapy.